Evaluating the English Language Courses for Engineers in Pakistan Using an ESP Approach - Pervaiz, Azhar; KhudaDad, Kaynat (Journal of Communication and Cultural Trends, 2023)
The current study attempted to evaluate the English language courses taught in engineering universities for prospective engineers in Pakistan. A syllabus for any degree or certificate, especially professional degrees, provides a road map for learners. Therefore, most of the students with professional degrees including engineering, think that there is no need to waste their energy on subjects that are not directly related to their profession. Resultantly, the subject of English could not take the prime position in the engineering universities in Pakistan. Therefore, in the current study both the questionnaires and interviews were set consisting of three categories. The first category of sample comprised of 50 male and female students who have completed at least one course of English mostly from Lahore based universities. The second category of sample was taken from twenty English language teachers from other two universities in Lahore and the third category of sample was taken from twenty professional engineers in Pakistan. The study is significant as it attempted to evaluate the existing syllabus of Pakistani engineering universities as the syllabus of engineering in Pakistan is at par with the syllabuses provided by organizations of international standards, such as IEEE (Institute of Electrical and Electronics Engineers, Inc.). The results showed that the syllabus designed for engineering students was not sufficient to meet their professional needs. In this regard, the study may also be helpful for the committee of curriculum revision constituted by the Higher Education Commission (HEC), Pakistan.